RELATIVIZATION STRATEGIES OF APPLICATIVE ARGUMENTS RELATION IN BELITONG - I Nyoman Pasek Darmawan; Vindi Kaldina (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
On the basis of a detailed study of the applicative phenomenon in the Belitong language done by Darmawan and Kaldina (2022), this paper suggests its symmetrical treatment specifically in terms of NP’s relativization strategies. Through the descriptive-qualitative research method, this paper identifies and describes the most accessible relativization strategies in Belitong as derived from applicative constructions. The data were collected through elicitation, unstructured open-ended interviews, and document analysis of previous literature works on the Belitong language. The data analysis process proceeded by employing qualitative data techniques and a careful linguistic typological approach, RG. The results of this study showed that: (1) A gap strategy is employed in direct relativization, and it accommodates the revaluation of core arguments (S and O), (2) indirect relativization allows the application of the passivization strategy on object properties of applicative constructions. Interestingly, two types of passives are permissible to account for indirect relativization. In type 1, the advancement of an O as the head of RC causes the demotion of the initial S to chômeur, morphologically marked by the prefix de- preceding the verb. However, in the passive type 2, the base subject does not reside in chômeur, yet it becomes the subject of the main clause with no prefix appearing on the verb.